Kwestia bogactwa i ubóstwa w Kościele imperialnym na zachodzie w IV i V wieku. Próba syntezy zagadnienia - Kasprzak, Dariusz (Vox Patrum, 2011)
I considered the different views regarding the issues of possession, wealth and poverty in the fourth and fifth century. I focused on the concepts of the fifth-century theologian (St. Ambrose, the Bishop of Milan, St. Augustine the Bishop of Hippo), pioneers of the western monastic theology and also the earliest monastic theologians and the heterodox pelagianist writers. They regarded soteriological perspective of Christianity. In that early period the socio-economic view did not constitute a doctrine. We can distinguish two essential approaches to the issue of possession in the teaching of the Church Fathers in the fourth and fifth century: a realistic and a pessimistic attitude. (The optimistic version regarded the possession of wealth as the result of Divine Protection and as a reward for pious Christian life. Both those models presumed that all the earthly goods were created by God and that people are only the temporary stewards of the goods given them for use. The realistic approach emphasized that everything which God has made was good and there was nothing wrong with owning possessions but it denounced the unjust means by which it is sometimes achieved or used. The pessimistic approach of Anchorites (monasticism, orthodox and heterodox ascetics) accepted the possession of goods which were made with one’s own hands. Everything which was not necessary should be given as alms. Coenobitic monks didn’t have anything of their own because everything belonged to the monastery. Their superior decided how everything could be used. The heterodox followers of Pelagius condemned shared of private property at all, and shared the view that voluntarily poverty was the only possible way for Christian.